Groundwater Flow and Transport Model in Cecina Plain (Tuscany, Italy) using GIS processing - Armellini, Riccardo; Baldini, Elena; Del Seppia, Dario; Franceschini, Fabrizio; Gori, Natacha; Menichetti, Stefano; Tessitore, Stefano (Acque Sotterranee - Italian Journal of Groundwater, 2015)
This work provides a groundwater flow and transport model of trichlorethylene and tetrachlorethylene contamination in the Cecina's coastal aquifer. The contamination analysis, with source located in the Poggio Gagliardo area (Montescudaio, Pisa), was necessary to optimize the groundwater monitoring and remediation design. The work was carried out in two phases: • design of a conceptual model of the aquifer using GIS analysis of many stratigraphic, chemical and hydrogeological data, collected from 2004 to 2012 in six aqueduct wells; • implementation of a groundwater flow and transport numerical model using the MODFLOW 88/96 and MT3D code and the graphical user interface GroundWaterVistas 5. The conceptual model hypothesizes a multilayer aquifer in the coastal plain extended to the sandy-clay hills, recharged by rainfall and by the Cecina River. The aquifer shows important hydrodynamic features affecting both the contamination spreading, due to the presence of a perched and heavily polluted layer separate from the underlying productive aquifer, and the hydrological balance, due to a thick separation layer that limits exchanges between the river and the second groundwater aquifer. The numerical model, built using increasingly complex versions of the initial conceptual model, has been calibrated using monitoring surveys conducted by the Environmental Protection Agency of Regione Toscana (ARPAT), in order to obtain possible forecast scenarios based on the minimum and maximum flow periods, and it is currently used as a tool for decision support regarding the reclamation and/or protection of the aquifer. Future developments will regard the implementation of the multilayer transport model, based on a new survey, and the final coupling with the regional hydrological model named MOBIDIC.